Determine alternatives environmental sustainability of bauxite downstream industry management through integration MICMAC - ANP method: a case study of Ketapang Industrial Area, Ketapang Regency, West Kalimantan Province. Issue 1 (1st November 2022) - Hendrik,; Fauzi, A; Widiatmaka,; Suryaningtyas, D T; Firdiyono, F
Abstract: Red mud industrial cluster site is associated with increased risk of dam failure and there is an urgent need to address the environmental problem caused by the hazardous and toxic waste of red mud in alumina industry. The objective of this study was to determine the alternatives waste management of Ketapang Industrial Area by integrating the MICMAC-ANP method. The data source is from forum group discussion (FGD) and an in-depth interview with experts. The results of the study using the MICMAC showed that the relay variables were human resources, recycling technology, and raw material guarantee. Furthermore, integrated MICMAC-ANP method showed that the agreed-upon solution for environmental management is to form a partnership among companies, Ketapang industrial management, and regional-owned enterprises, with the regional-owned enterprise having the largest share of the product produced from economic waste. This can be seen from the weighting of each element that indicates the regional-owned enterprise element has the greatest weight, which is 0.4. Meanwhile, waste disposal criterion is quite important (0.44) in determining alternative environmental sustainability management of downstream bauxite industry. The primary consideration to achieve environmental sustainability management of the downstream bauxite industry are CSR, Labor, Tax, PPM, and transportation, which have a weight that is relatively similar (0.2). Regionally owned enterprises (0.4) play the most important roles in environmental management of the sustainable bauxite mining downstream industry related to economic waste management (the use of red mud).